Evaluation of Knowledge, Perception, and Risk Awareness About Breast Cancer and Its Treatment Outcome Among University of Gondar Students, Northwest Ethiopia - Gebresillassie, Begashaw Melaku; Gebreyohannes, Eyob Alemayehu; Belachew, Sewunet Admasu; Emiru, Yohannes Kelifa (Frontiers in Oncology, 2018)
Background: Breast cancer is among the most common life-threatening public health problems of global concern including Ethiopia. Knowledge and awareness about the disease will help to reduce the number of cases who present at late stages of the disease. The objective of this survey was to assess the knowledge, perception and risk awareness about breast cancer among female medical and health science students of University of Gondar, Ethiopia. Methods: A cross sectional survey was conducted from May 03 to June 01, 2017 at University of Gondar, Ethiopia. Three hundred students were proportionally selected from nine departments using simple random sampling method. Using a structured questionnaire data on risk factors, symptoms and perception about breast cancer and its management approach was collected. Data were entered to and analyzed using SPSS version 21. Results: A total of 300 students had fully completed the survey making the response rate 95.24. The participants’ mean age was 21.4 years with the standard deviation(SD) of 2.13 years. The overall level of knowledge on breast cancer was low. Majority of the participants were unaware for complex risk factors such as first child after the age of 30 years (51%), early onset of menses (55.3%), and menopause after the age of 55 years (47.7%) are liked with breast cancer even though they acknowledged old age, family history, and smoking as possible risk factors for breast cancer. Majority of the study participants had also correct beliefs about breast cancer management and its outcomes. However, they had negative perception of breast cancer treatment by considering it to be a long-term and painful process. In binary logistic regression analysis department(p=0.000) and year of study(p=0.008) were found to be an independent predicting factors for knowledge among the study participants. Conclusions: The overall level of knowledge on breast cancer and clinical breast examination guidelines was found to be low even though majority had positive perception towards the treatment and its outcomes.